Synthesis of NiSe nanorod array structure as a binder-free cathode for an aqueous rechargeable Ni–Zn battery. (13th July 2022) - Zhang, Daojun; Jiang, Bei; Liu, Yang; Zhang, Jingchao; Wang, Yinhuan; Wei, Minglun; Zhang, Renchun; Li, Chaowei; Huang, Liangliang
Abstract : Co0.33 Ni0.67 Se nanorod array electrode synthesized by a simple two-step solvothermal method on Ni foam and demonstrated good electrochemical performances for supercapacitor and aqueous rechargeable Ni–Zn battery. Abstract : Rechargeable electrochemical energy storage devices have attracted extensive attention all over the world due to the increasing energy crisis and environmental pollution. Transition metal Ni-based sulfides are deemed as among the best potential electrode materials for supercapacitors and Ni–Zn batteries. A series of Ni-based selenide nanorod arrays were grown in situ by a simple two-step solvothermal method in this work. Compared with the coexistence of two-phase nickel selenide obtained directly from selenide Ni foam, the first step of solvothermal pretreatment followed by the selenization process tends to get a single pure phase. Furthermore, a Co0.33 Ni0.67 Se nanorod array structure with excellent electrochemical performance can be obtained by introducing Co ions in the first step and adjusting the pH value of the selenization solution. The results show that the Co0.33 Ni0.67 Se nanorod array can reach a high capacity of 0.241 mA h cm −2 at a current density of 1 mA cm −2 as a supercapacitor electrode. When assembled into a Co0.33 Ni0.67 Se//Zn battery, it exhibits a high capacity of 0.251 mA h cm −2 at a current density of 1 mA cm −2 . After 1000 cyclic charge/discharge runs, the battery loses 46% of the original capacity. In addition, it exhibits an excellent energy density of 0.428 mW h cm −2 corresponding to the power density of 1.7 mW cm −2 . In this work, we explored the artificial control of the phase transformation in the synthesis process to make it tend to the hexagonal phase NiSe and Co0.33 Ni0.67 Se nanorod arrays with better electrochemical performance, so as to provide a powerful solution for the optimization of the cathode material for aqueous rechargeable Ni–Zn batteries.